The Burden of Tetanus in Uganda - Nanteza, Barbara; Galukande, Moses; Aceng, Jane; Musinguzi, Joshua; Opio, Alex; Mbonye, Anthony K.; Mukooyo, Eddie; Behumize, Prosper; Makumbi, Fredrick (Springerplus, 2016)
The successful scale-up of safe male circumcision (SMC) in Uganda has been hinged on client’s safety and quality of services. However, after the recent three tetanus deaths after circumcision a review of all tetanus cases in one of the hospitals where the cases occurred was initiated. This was to ascertain the potential for an association between tetanus infection and circumcision. Routinely collected national data were also reviewed to determine the burden of tetanus in Uganda and contextualize these incidents.
Keywords: Burden; Tetanus